Swanson's family medicine review a problem-oriented approach. - Swanson, Richard W.; Tallia, Alfred F.; Scherger, Joseph E.; Dickey, Nancy (Saunders/Elsevier, 2013)
A guide that helps those who are preparing to take the American Board of Family Medicine (ABFM) examination. It focuses on various concepts relevant to primary care and family medicine practice.